1995
DOI: 10.1002/pola.1995.080330719
|View full text |Cite
|
Sign up to set email alerts
|

Growth of poly(methyl methacrylate) particles in three‐component cationic microemulsions

Abstract: Polymerization of methyl methacrylate (MMA) has been studied in ternary microemulsions which were stabilized by tetradecyltrimethylammonium bromide (TTAB) or stearyltrimethylammonium chloride (STAC). The sizes of MMA‐swollen polymer particles (Rh) increased continuously during polymerization. This is in contrast to that of the styrene system, where Rh increased very rapidly to a maximum and then decreased continuously towards a constant value. The continuous growth of PMMA particles at 60°C are discussed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The heterogeneous nucleation of PMMA during synthesis by the differential microemulsion polymerization was a key factor to enhance the rich syndiotactic configuration with the high concentration of PMMA when compared with other microemulsion polymerization techniques 5–13…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterogeneous nucleation of PMMA during synthesis by the differential microemulsion polymerization was a key factor to enhance the rich syndiotactic configuration with the high concentration of PMMA when compared with other microemulsion polymerization techniques 5–13…”
Section: Resultsmentioning
confidence: 99%
“…A Bruker Biospin DPX‐300 NMR spectroscometer (Bruker AXS Inc., Madison, WI) was used for 1 H‐NMR analyses at 300 MHz with CDCl 3 solutions at room temperature. The tacticities of the samples were characterized from the integrated ratios of the syndiotactic (rr), isotactic (mm), and heterotactic (mr) triad signals of α‐methyl protons, which occur at 0.81, 0.99, and 1.18 ppm, respectively 11, 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -27 Gan and coworkers produced PMMA in ternary microemulsions using the cationic surfactants stearyl trimethylammonium chloride (STAC), cetyl trimethylammonium bromide (CTAB), and dodecyl trimethylammonium bromide (DTAB) with either a water-soluble or an oil-soluble initiator, and found that the longer the hydrophobic chain length of the surfactant, the smaller the latex particles. 23 Kaler and coworkers also have produced small latexes from styrene and from several different methacrylic esters using cationic surfactants. 12,19,24 -26 Larpent and Tadros found optimum mixtures of nonionic surfactants, to form microemulsions of MMA and of styrene in water, and produced small latex particles at varied surfactant-to-monomer ratios using ascorbic acid/hydrogen peroxide as a redox initiator.…”
Section: Introductionmentioning
confidence: 97%
“…Microemulsion polymerization has been studied by several groups. Some examples areas follows: Gan and coworkers produced PMMA in ternary microemulsions using the cationic surfactants stearyl trimethylammonium chloride (STAC), cetyl trimethylammonium bromide (CTAB), and dodecyl trimethylammonium bromide (DTAB) with either a water‐soluble or an oil‐soluble initiator and found that the longer the hydrophobic chain length of the surfactant, the smaller the latex particles 23. Kaler and coworkers also have produced small latexes from styrene and from several different methacrylic esters using cationic surfactants 12, 19, 24–26.…”
Section: Introductionmentioning
confidence: 99%